Impact of tree plantations on the dynamics of soil aggregates in urban degraded lands in the dry tropics. (28th September 2021) - Singh, Sunil; Singh, Mahesh Kumar; Kumar, Chandra Mohan; Soni, Priyanka; Ghoshal, Nandita
Abstract: The impact of land‐use change in an urban ecosystem on soil aggregate dynamics and soil carbon storage was studied through two annual cycles under five land uses. All the land uses namely: (1) natural mixed vegetation (NV) growing in a protected area; (2) grass fallow (GF); and tree plantations of (3) Cassia siamea (CP); (4) Jatropha curcas (JP); and (5) Tectona grandis (TP) were grown on urban degraded waste lands in a dry tropical region of India. Proportions of soil aggregate fractions, their stability, and soil carbon storage were analyzed at upper (00–15 cm), and lower (15–30 cm) soil depths during the rainy, winter, and summer seasons. Across all the land uses and at both the soil depths, the proportion of macroaggregate was highest during summer and lowest during the rainy season, whereas the reverse trend was observed for mesoaggregate. The annual mean proportion of macroaggregate decreased while meso‐ and microaggregates increased, with increasing soil depth across all the land uses. At the upper layer, the trends of macroaggregate, aggregate stability, and soil C storage were NV > CP > JP > TP > GF whereas at lower depth, the trend was NV > TP > CP > JP > GF. Across all the land uses in both the depths, soil C storage was strongly and positively correlated with annual mean fraction of soil macroaggregate. All tree plantations improved soil properties considerably as compared to GF at upper soil layer, yet TP reached near NV in these soil properties at lower depth. Soil aggregate fractions may be used as an index of carbon storage capacity in the urban ecosystems.